PHENOLOGY OF HARD TICKS IN SOUTHERN URAL - P. I. Khristianovsky; V. V. Belimenko; I. V. Byistrov; E. V. Novosad (Российский паразитологический журнал, 2016)
Objective of research. Hard ticks as blood sucking ectoparasites and vectors of animal and human diseases are considered as one of the most important arthropods. Ticks can transmit a variety of diseases among livestock. They are distributed throughout Southern Ural, affecting cattle, horses, sheep, goats and dogs.Materials and methods. The aim of the survey is to estimate the recent distribution, host-parasite relationships, seasonal activities of the hard ticks in Southern Ural, based on original material collected within 2000-2013.Results and discussion. The fauna of ticks in Southern Ural is represented by following species: Dermacentor marginatus Sulzer, 1776 (70,2%), Dermacentor reticulatus Fabricius, 1794 (22,3%), Rhipicephalus rossicus Yakimov et Kohl-Yakimova, 1911 (3,2%), Hyalomma scupense Schulze, 1918 (1,8%), Hyalomma detritum Schulze, 1919 (1,6%), Ixodes ricinus Linnaeus, 1758 (0,9%). Genus Dermacentor is dominant in region (92,5% of total number). D. marginatus considerably prevails above D. reticulatus (70,2 and 22,3%). Other species meets in insignificant quantity.